2005
DOI: 10.1111/j.1365-2036.2005.02443.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory gene signature in ulcerative colitis with cDNA macroarray analysis

Abstract: SUMMARYBackground: Most array analyses of ulcerative colitis have focused on identifying susceptibility genes for ulcerative colitis. Aim: To clarify the changes in gene expression during inflammation in ulcerative colitis colon mucosa using cDNA macroarray. Methods: From 23 ulcerative colitis patients, 16 each of inflamed and non-inflamed specimens (total 32 samples for individual analysis) were obtained by colonoscopic biopsy. Eighteen of the 32 samples, used for pairwise analysis, consisted of nine sample p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 41 publications
(40 reference statements)
5
21
0
Order By: Relevance
“…The expression of lipocalin-2 was not different among treatments in the chronic model, and it may be because it has been used as a marker of neutrophil inflammation in conditions such as ulcerative colitis and proctitis. 19 Histological analysis of bladder sections demonstrated the presence of neutrophils in the acute model but very few or none in the chronic model. Lipocalin-2 expression in ovariectomized mice treated with 17␤-estradiol was slightly increased when compared with control mice as reported previously in the uterus.…”
Section: Discussionmentioning
confidence: 96%
“…The expression of lipocalin-2 was not different among treatments in the chronic model, and it may be because it has been used as a marker of neutrophil inflammation in conditions such as ulcerative colitis and proctitis. 19 Histological analysis of bladder sections demonstrated the presence of neutrophils in the acute model but very few or none in the chronic model. Lipocalin-2 expression in ovariectomized mice treated with 17␤-estradiol was slightly increased when compared with control mice as reported previously in the uterus.…”
Section: Discussionmentioning
confidence: 96%
“…3), suggesting that this network may be correlated with the colonic cell differentiation induced by SB. Indeed, PMP22 [29], RB1 [30], NDRG1 [31], IGF2R [32], IGF2 [33], JUNB [34], TIMP1 [35] and THRA [36] have been reported to be expressed in the small intestine or colon. This network includes IGF2 at its center.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding for chemokines, markers of neutrophil activation, and anti-inflammatory factors are upregulated in humans with CE. 11,12 Moreover, disturbances in expression of genes encoding for proteins involved in innate or adaptive immunity, detoxification, and nuclear transcription are important in the pathogenesis of mucosal inflammation in mice with experimentally induced colitis. 13,14 The objectives of the study reported here were to determine gastrointestinal mucosal gene expression patterns in dogs with CE, compare results with those for healthy control dogs, and determine whether gene expression differs among dogs with CE of various severities.…”
mentioning
confidence: 99%